Tolerance to irrigation water salinity in physalis plants: productive aspects (Bioscience Journal, 2020)
The cultivation of non-traditional fruits has gained ground in the horticulture sector, but which, in certain situations, are plants that require previous studies related to soil adaptability, climate, and irrigation water quality. In this sense, this work aimed to evaluate the effects of irrigation water salinity on Physalis peruviana L. (fisális) plants in the different growth phases. The experimental area was installed on the premises of the Federal University of Campina Grande, adopting a casualized block design, with four saline levels of irrigation water (0.3; 1.2; 2.1 and 3.0 dS m-1) and five repetitions per treatment. The variables analyzed were: stem diameter, plant height and number of leaves every 15 days, leaf area at 55 days after transplanting, number of side branches, number of flower buds, number of flowers, average fruit weight, polar diameter, and equatorial diameter of fruits, number of fruits per plant and productivity. According to the results, the plants were tolerant to saline levels of irrigation water of up to 3.0 dS m-1, without prejudice to the phenological and productive characteristics of the crop. The unitary increase in the salinity of the irrigation water did not result in damage to the physiological characteristics of the plants until the 60 days of transplanting.